Effect of hCG, estradiol -17 Î² and progesterone on leaching and formation of FSH receptors in follicular compartments - Majumdar, A C; Sharma, G Taru (The Indian Journal of Animal Sciences, 2012)
Studies were undertaken on the role of hCG, If any in leaching out of FSH receptors in follicular compartment using isolated >5 mm nonatretic goat follicles in culture. Role of estradiol-17 Î² m in presence or absence of progesterone on formation of FSH receptors in follicular compartment in these cells were also studied using immunohistochemical techniques. 1 treatment of follicle with hCG for 8 hr, leaches out almost all the FSH receptors of follicular fluid. Further treatment of these follicles with estradiol in presence of progesterone for 16 hr enhanced FSH receptors in the follicular fluid. However only estradiol treatment enhanced receptor formation in the theca and granulosa cells. It may be concluded from the study that hCG helps in leaching out of follicular fluid receptors, which are formed under the influence of estradiol. Though follicular fluid receptors form in presence of progesterone, the receptors on granulosa cells form only in the absence of progesterone.